A pintura não figurativa poética contemporânea de Joan Mitchell sob o olhar de Deleuze e a lógica da sensação - Moreau, Talita da Silva (2023)
Joan Mitchell, contemporary American artist, author of hundreds of paintings and engravings that summarize in her own way the history of non-figurative pictorial language. His work made possible line-based research in the philosophical field, at the intersections of Art and Philosophy, analytical work linked to the History, Society and Culture line of research. During the incursion into the aesthetic space of the 20th century, the presence of Gilles Deleuze and Félix Guattari was essential, especially the writings of the former, which provided the opportunity to deepen considerations on the autonomy of the work of art insofar as artistic creation abandons the classic paradigm, centered on the canon of beauty that corresponds to it and too dependent on figuration, on representation. The research approached the art of Joan Mitchell and the philosophy of difference, suggesting possibilities that are freed from representation. What is seen when figuration leaves the artistic space? We can summarize the research problem with this question, there is no ready, definitive answer; there is the opening-exit to make visible the forces of sensations. The objective of the work, which is now provisionally a dissertation, was to understand the percepts and affects that capture the imperceptible dispersed in the plane of immanence, something indiscernible and that can be opened to the logic of sensation.